The influence of Inclusive Pedagogies on Student Motivation and Classroom Atmosphere. The use of Video Narrative as an aid to Teacher Metacognition. - Ball, Sally (2017)
The use of video based technology in classrooms is an increasing focus in contemporary literature, and this study seeks to investigate the opportunities afforded by such systems to encourage reflective practice amongst teachers. With an emphasis on the potential of such reflection to enhance the metacognitive awareness of education professionals, the effects of a greater self-understanding are positioned in terms of their impacts on the interpretation of inclusive pedagogies, and subsequently student motivation and classroom atmosphere. Arising from an extensive review of existing research relative to both video narratives and classroom practices within an era of performativity, ideas of post-modernist subjectivity interact with thematically analysed primary data to advance the suggestion that reconceptualising accountability as responsibility is a necessary first step in advancing education along heuristic lines. Whilst opportunities for further research are presented as a means of safeguarding standardisation obsessions, embryonic conclusions that strive to accommodate professional vulnerabilities within dominant philosophies of education are offered.